Polymorphisms in the multiple drug resistance protein 1 and in P-glycoprotein 1 are associated with time to event outcomes in patients with advanced multiple myeloma treated with bortezomib and pegylated liposomal doxorubicin - Buda, Gabriele; Ricci, Deborah; Huang, C. Chris; Favis, Reyna; Cohen, Nadine; Zhuang, Sen H; Harousseau, Jean-Luc; Sonneveld, Pieter; Bladé, Joan; Orlowski, Robert Z (Annals of hematology, 2010)
Single nucleotide polymorphisms (SNPs) in the multiple drug resistance protein 1 (MRP1) and P-glycoprotein 1 (MDR1) genes modulate their ability to mediate drug resistance. We therefore sought to retrospectively evaluate their influence on outcomes in relapsed and/or refractory myeloma patients treated with bortezomib or bortezomib with pegylated liposomal doxorubicin (PLD). The MRP1/R723Q polymorphism was found in five subjects among the 279 patient study population, all of whom received PLD + bortezomib. Its presence was associated with a longer time to progression (TTP; median 330 vs. 129 days; p = 0.0008), progression-free survival (PFS; median 338 vs. 129 days; p = 0.0006), and overall survival (p = 0.0045). MDR1/3435(C > T), which was in Hardy-Weinberg equilibrium, showed a trend of association with PFS (p = 0.0578), response rate (p = 0.0782) and TTP (p = 0.0923) in PLD + bortezomib patients, though no correlation was found in the bortezomib arm. In a recessive genetic model, MDR1/3435 T was significantly associated with a better TTP (p = 0.0405) and PFS (p = 0.0186) in PLD + bortezomib patients. These findings suggest a potential role for MRP1 and MDR1 SNPs in modulating the long-term outcome of relapsed and/or refractory myeloma patients treated with PLD + bortezomib. Moreover, they support prospective studies to determine if such data could be used to tailor therapy to the genetic makeup of individual patients.